A conceptual analysis of system responses to the issue of problematic sexual behaviors in children and recommendations for future work in Children’s Advocacy Center multidisciplinary teams - Harris, Mary; Lanni, Diane; Svendsen, Sasha (Frontiers in Psychiatry, 2023)
Problematic sexual behavior (PSB) in children is a common, yet frequently misunderstood and mishandled issue facing communities. Because of the intersection of children both causing harm and being harmed, societies across the globe struggle with whether to punish or support during these times. For Children's Advocacy Centers (CACs), whose mandate it is to support victimized children, this tension is exacerbated. CACs have historically relied on identifying a "perpetrator" and "victim" when providing their services, however PSB displaying youth do not fit this classic dichotomy. Compared with other children, PSB displaying youth are more likely to experience greater incidents and types of violent childhood trauma, have increased parent instability, decreased familial support, and struggle with co-occurring mental health diagnoses. Due to the stigma and fear surrounding sexual behaviors in children and systemic barriers including varied definitions of PSB, uncertainty regarding how to respond within the context of child-serving roles, and the criminalization of children's behaviors, access to supportive services is complicated and challenging. Treatment completion rates for this population are as low as 13%, despite most methods being short-term, noninvasive, and community based. This conceptual analysis paper identifies five key themes in the literature that influence these barriers and proposes an interdisciplinary approach for CAC multidisciplinary teams (MDTs) to better support this vulnerable population.